Kedudukan Istri Dan Anak Dalam Pernikahan Di Bawah Tangan Menurut UU No. 1 Tahun 1974 Tentang Perkawinan (Studi Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010) - Pijar Bima Y, Rischi; , Mutimatun Ni'ami, S.H., M.Hum.; , Muchamad Iksan, S.H., M.H. (2016)
The purpose of this study was to describe the position of the wife and children of the marriage under the hand, according to Law No. 1 Year 1974 on Marriage. This research includes juridical empirical legal research is to discuss the implementation and examine the implementation of legal provisions in practice. Data were analyzed using qualitative analysis. The results showed that: First, the Status wife in marriage under the hand, according to Law No. 1 Year 1974 on Marriage is always the weaker party position because: do not have proof of authenticity as a wife legitimate, the wife does not have the legal power, difficult to get right to the treasures, and the position is not good socially wife; Secondly, the position of the child of a marriage under the hand According to Law No. 1 Year 1974 on Marriage after the MK Decision No. 46 / PUU-VIII / 2010, the child of a marriage that is not listed can be a legitimate child and have a civil relationship with his father; Third, the solution can be taken to strengthen the position of the wife and child of a marriage under the hand is Ithbat marriage, remarriage (tajdid), begging Court Decision on Approval of the Son, and does not do marriage under hand. Keywords: marriage under hand, the position of wife and children